Ec STRATEGI GURU DALAM MENINGKATKAN KECERDASAN VERBAL-LINGUISTIK PADA MATA PELAJARAN BAHASA INDONESIA KELAS I DI SDN MAGUWOHARJO 1 - Effi, Effiana Cahya Ningrum; Maemonah, Maemonah ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2022)
The purpose of this research was to find out the teacher's strategy in increasing verbal-linguistic intelligence in Indonesian class I at SDN Maguwoharjo 1. This study used a descriptive qualitative research method using data collection techniques through interviews, observation and documentation. With class I-B participants totaling 27 students and class I-B teacher informants. The results showed that there were 5 students who were still lacking in reading and writing skills. (verbal-linguistic intelligence). So that there are several strategies carried out by the teacher in increasing verbal-linguistic intelligence in Indonesian subjects in class I-B including: learning media letter cards, letter posters, syllable cards and word cards, singing activities, video learning media, peer tutors, setting the place sit down and give extra study. The letter card media strategy and the provision of additional learning after school by the teacher were very effective in increasing students' verbal-linguistic intelligence, especially in the aspects of reading and writing. From some of these strategies, teachers can develop them using learning media and innovative methods for students who experience deficiencies in reading and writing skills. Keywords : teacher strategy, linguistic intelligence, Indonesian, Primary School